The Impact of Gamification on Retail Investor Behavior: A Behavioral Finance Perspective - Tomy Prasetia; Lista Meria; Kursih Sulastriningsih; Nolan Liam (Pandawan Sejahtera Indonesia, 2026)
The rapid growth of commission-free, mobile-based trading apps has made it easier for retail investors to participate in financial markets while introducing gamification features that influence how they make decisions. This study examines how these gamified elements affect trading frequency, risk-taking, and cognitive biases, as well as the ethical and regulatory implications that arise. We conducted a systematic literature review of studies published between 2021 and 2025, analyzing peer-reviewed articles and regulatory reports focused on behavioral finance, gamification psychology, and fintech governance. The research asks three main questions: How do gamification features influence trading frequency? How do they affect investors’ risk-taking behavior? Which behavioral biases are most reinforced? Based on these, we formulated hypotheses to explore the relationships in detail. The findings show that animations, rewards, and social comparison features increase trading activity, encourage higher risk tolerance, and strengthen biases such as overconfidence and the dis-position effect. Ethical concerns, including misaligned incentives, potential behavioral manipulation, and weaker investor protection, highlight the need for responsible platform design and thoughtful regulatory oversight. Overall, the study contributes by connecting behavioral finance theory with gamification psychology, offering insights into the psychological mechanisms at play in digital investing. Future research should empirically test these hypotheses, investigate long-term investor outcomes, and develop ethical guidelines that balance engagement with responsible investing practices.